2015
DOI: 10.1038/ja.2014.171
|View full text |Cite
|
Sign up to set email alerts
|

Novel terpenes generated by heterologous expression of bacterial terpene synthase genes in an engineered Streptomyces host

Abstract: Mining of bacterial genome data has revealed numerous presumptive terpene synthases. Heterologous expression of several putative terpene synthase genes in an engineered Streptomyces host has revealed 13 newly discovered terpenes whose GC-MS and NMR data did not match any known compounds in the spectroscopic databases. Each of the genes encoding the corresponding terpene synthases were silent in their parent microorganisms. Heterologous expression and detailed NMR spectroscopic analysis allowed assignment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 14 publications
2
58
0
7
Order By: Relevance
“…The connectivity of the remaining diastereotropic protons H4, H6, H8, and H9 were readily determined from the long-range 1 H- 13 C coupling constants between the respective protons and their neighboring carbon atoms. Our NMR assignments agree with those recently reported by Yamada et al, except we assigned the resonances at H6 to 0.85 ppm, 1.77 ppm and at H4 to 1.26 ppm, 1.84 ppm (15).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The connectivity of the remaining diastereotropic protons H4, H6, H8, and H9 were readily determined from the long-range 1 H- 13 C coupling constants between the respective protons and their neighboring carbon atoms. Our NMR assignments agree with those recently reported by Yamada et al, except we assigned the resonances at H6 to 0.85 ppm, 1.77 ppm and at H4 to 1.26 ppm, 1.84 ppm (15).…”
Section: Resultssupporting
confidence: 82%
“…In the same year, Nakano et al reported the characterization of two additional terpene synthases, a monoterpene cyclase that produced 1,8-cineole and a promiscuous acyclic terpene synthase that produced linalool and nerolidol (13,14). While this manuscript was in the final stages of preparation, the function of an additional terpene synthase, which is a protein variant of the subject of this investigation, was reported to synthesize a linear triquinane of undefined stereochemistry (15). The Significance This paper describes a novel strategy for predicting the function of terpene synthases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds produced were evaluated by comparison with the mass spectra of the corresponding reference compounds in the National Institute of Standards and Technology (NIST)/United States Environmental Protection Agency (EPA)/National Institutes of Health (NIH) MS Library (2014 version). The generation of previously unidentified terpene products is described in SI Materials and Methods, whereas the NMR structure elucidation of all previously unidentified compounds is described in another work (54). The large-scale preparation of terpenoid metabolites is described in SI Materials and Methods.…”
Section: Heterologous Expression Of Genes Encoding Bacterial Terpenementioning
confidence: 99%
“…My laboratory has published more than a dozen papers in Journal of Antibiotics, covering our studies of both terpenoid and polyketide biosynthesis. [63][64][65][66][67] SABBATICAL AT THE UNIVERSITY OF CAMBRIDGE AND THE JOHN INNES CENTRE In 1989, after 6 years as Chair of the Brown Chemistry Department, I spent a 1-year sabbatical leave at the University of Cambridge. My host was Dr Chris Abell, who had been a postdoc in my laboratory in 1982-1983 before returning to a faculty position in the Department of Chemistry in Cambridge.…”
Section: Visiting Japanmentioning
confidence: 99%